Kualitas Semen Segar dan Produksi Semen Beku Sapi Pejantan Madura pada Musim yang Berbeda - Komariah; R. I. Arifiantini; M. Aun; E. Sukmawati (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
Variation among breed and seasons were speculated influence to the quality of fresh semen bull. The aim of this research was to evaluate the quality of fresh semen and the potential of frozen semen production madura bull in rainy and dry seasons at Lembang Artificial Insemination Center (AIC). This research used secondary data of semen production from January to December 2015. In this research were used 5 bulls. The observed variables for macroscopic characteristics of fresh semen were volume, color, pH, and consistency, and microscopic characteristics of fresh semen were mass movement, motility, and concentration of spermatozoa. It could be concluded that the quality of fresh semen and the potential of frozen semen production of several madura bulls were relatively different in the rainy and dry seasons.